Resources For Implementing The Smart Indonesia Program In An Effort To Equalize Education: Sumber Daya Penerapan Program Indonesia Pintar Dalam Upaya Pemerataan Pendidikan - Rifqi Abdillah, Moch; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2022)
The Smart Indonesia Card Policy as a form of government program launched to address the problem is still found in many students who are still of school age but drop out of school due to financial difficulties given to students from Elementary School or Madrasah Ibtida'iyah, Junior High School or Madrasah education levels Tsanawiyah, Vocational High School or Senior High School or Madrasah Aliyah. One of the regencies or cities in East Java that has realized acceptance of the Smart Indonesia Program is Sidoarjo Regency. including the class as students whose parents are underprivileged or students whose parents are registered as owners of PKH and KKS cards. However, in its implementation there are still some obstacles, such as those at SDN Kenongo 1, namely the acceptance of the Smart Indonesia program is still uneven and has decreased when implementing it due to the lack of monitoring and data collection carried out by homeroom teachers on students, besides that, socialization to parents and guardians of students is only carried out when taking report cards only. The purpose of this study is to find out how the resources for implementing the smart Indonesia program are in an effort to equalize education. This research is a qualitative descriptive study using a purposive sampling technique in determining informants. Data collection techniques were carried out by interview, observation, and documentation.